KONSORSIUM MIKROBA LINTAS KINGDOM DALAM BIOREMEDIASI LIMBAH CAIR DENGAN PENDEKATAN INTEGRATIF OMIK DAN EKOLOGI SINTETIS: SUATU LITERATURE REVIEW - syamsul; Hala, Yusminah (Universitas Cokroaminoto Palopo, 2025)
Wastewater bioremediation demonstrates substantially improved performance when employing cross-kingdom microbial consortia, as bacteria, fungi, and microalgae complement one another in carrying out successive stages of organic and persistent pollutant degradation. This review summarizes current findings on the functional mechanisms of such consortia, including metabolic division of labor, metabolite exchange, enzymatic complementarity, and the role of biofilms in maintaining community stability. The literature indicates that cross-kingdom systems are highly effective in removing pollutants such as hydrocarbons, synthetic dyes, pharmaceuticals, nutrients, and microplastics. The integration of omics approaches provides a clearer understanding of the genes, metabolic pathways, and cellular activities involved in degradation processes. Synthetic ecology contributes to strengthening consortium design through spatial arrangement, directed functional roles, and controlled interspecies interactions. Overall, cross-kingdom microbial consortia supported by omics analyses and synthetic ecological concepts offer a solid foundation for developing more efficient and sustainable. wastewater bioremediation systems.